2014
DOI: 10.1002/jemt.22334
|View full text |Cite
|
Sign up to set email alerts
|

17-beta-estradiol analog inhibits cell proliferation by induction of apoptosis in breast cell lines

Abstract: Microtubules are important targets when studying potential anticancer agents since disturbance of these microtubule dynamics results in cell cycle arrest and cell death.2-Methoxyestradiol is a naturally occurring metabolite that exerts antiproliferative activity and induces apoptosis. Due to limited biological accessibly and rapid metabolic degradation, several analogues were synthesized. This study investigated the antiproliferative influence of an 2-methoxyestradiol analogue, (8R, 13S, 14S, 17S)-2-Ethyl- 13-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 25 publications
2
18
0
1
Order By: Relevance
“…Distorted cell shape, high density of digit-like apical microvilli, formations of vacuoles, lysosomes and apoptotic bodies, heterochromatin, as well as fragmented DNA were detected in both cell lines by means of transmission electron microscopy. This observation is supported by a study where 17β estradiol analog-treated MDA-MB-231, MCF-7 and MCF-12A cells demonstrated the presence of apoptotic bodies and vacuoles [63]. Fragmented nuclei and apoptotic bodies were detected within tumorigenic cells that were exposed to combination compounds, which indicate late stages of apoptosis and also support previous cell cycle- and apoptotic quantification [28,62].…”
Section: Discussionsupporting
confidence: 70%
“…Distorted cell shape, high density of digit-like apical microvilli, formations of vacuoles, lysosomes and apoptotic bodies, heterochromatin, as well as fragmented DNA were detected in both cell lines by means of transmission electron microscopy. This observation is supported by a study where 17β estradiol analog-treated MDA-MB-231, MCF-7 and MCF-12A cells demonstrated the presence of apoptotic bodies and vacuoles [63]. Fragmented nuclei and apoptotic bodies were detected within tumorigenic cells that were exposed to combination compounds, which indicate late stages of apoptosis and also support previous cell cycle- and apoptotic quantification [28,62].…”
Section: Discussionsupporting
confidence: 70%
“…Cells were seeded (1,000,000) in a 25 cm 2 flask with an overnight attachment policy [23]. Subsequently, medium was discarded and cells were exposed to the compounds.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have indicated that BIRC5 contributes to tumourigenesis and progression of NSCLCs due to its apoptosis suppression functions [32,33]. Moreover, it has been reported that E2 can cause cancer cell apoptosis [34]. Therefore, we speculated that cell apoptosis was enhanced in SCNC after E2 treatment by up-regulating expression of CASP3 and affecting the relationship between CASP3 and IAP members (BIRC2, BIRC3 and BIRC5).…”
Section: Discussionmentioning
confidence: 92%